The role of megatides and relative sea level in controlling the deglaciation of the British–Irish and Fennoscandian ice sheets. (31st January 2018) - Scourse, J. D.; Ward, S. L.; Wainwright, A.; Bradley, S. L.; Uehara, K.
ABSTRACT: Key external forcing factors have been proposed to explain the collapse of ice sheets, including atmospheric and ocean temperatures, subglacial topography, relative sea level and tidal amplitudes. For past ice sheets it has not hitherto been possible to separate relative sea level and tidal amplitudes from the other controls to analyse their influence on deglaciation style and rate. Here we isolate the relative sea level and tidal amplitude controls on key ice stream sectors of the last British–Irish and Fennoscandian ice sheets using published glacial isostatic adjustment models, combined with a new and previously published palaeotidal models for the NE Atlantic since the Last Glacial Maximum (22 ka BP). Relative sea level and tidal amplitude data are combined into a sea surface elevation index for each ice stream sector demonstrating that these controls were potentially important drivers of deglaciation in the western British Irish Ice Sheet ice stream sectors. In contrast, the Norwegian Channel Ice Stream was characterized by falling relative sea level and small tidal amplitudes during most of the deglaciation. As these simulations provide a basis for observational field testing we propose a means of identifying the significance of sea level and tidal amplitudes in ice sheet collapse.